Feed additives for swine: Fact sheets – carcass modifiers, carbohydrate-degrading enzymes and proteases, and anthelmintics - Jacela, Jay Y.; DeRouchey, Joel M.; Tokach, Michael D.; Goodland, Robert D.; Nelssen, Jim L.; Renter, David G.; Dritz, Steven S. (My University, 2012)
There is increasing consumer demand for leaner and healthier pork products. Improvements in genetics, new technologies, and increased understanding of nutrition have become instrumental in helping producers meet this demand. Continued research also has led to the development of products that can be included in swine diets as carcass modifiers. A dietary carcass modifier is broadly defined as any component of the diet that alters the resulting carcass composition of pigs. Generally, the mechanism of action of carcass modifiers is aimed at increasing protein and muscle deposition while reducing fat deposition. These products vary in the mechanisms by which they modify carcass quality. In addition, not all carcass modifiers are approved for use in pig diets, for public-health reasons. Understanding the modes of action and differences between these products is important for safe and effective use.Swine diets are composed mostly of plant-based ingredients. Nutrients contained in these feedstuffs need to be broken down by the pig into simpler forms that will be used to support maintenance, growth, and reproduction. This poses a problem, because, unlike ruminants, pigs do not have the ability to efficiently digest plant components that have relatively high fiber content. Pigs lack specific enzymes needed to break down fiber. Supplementing swine diets with exogenous carbohydrate-degrading enzymes that break down fiber has become increasingly popular to potentially improve availability of nutrients from ingredients with high fiber content. Parasite control, in addition to control of viruses and bacteria, must be part of a comprehensive herd-health program in every swine production system. Gastrointestinal worm infections may result in significant economic losses. Signs of infection are general and not readily apparent, since worm infections rarely cause elevated mortality levels. Some worms commonly found in pigs are roundworms (Ascaris suum), nodular worms (Oesophagostomum species), intestinal threadworms (Strongyloides ransomi), whipworms (Trichuris suis), kidney worms (Stephanurus dentatus), and lungworms (Metastrongylus species). Anthelmintics or “dewormers” are chemical substances that can be added to pig diets to control parasitic worms.
Keywords: Swine; Carcass modifiers; Proteases; Anthelmintics; Carbohydrate-degrading enzymes